Microform holoprosencephaly with bilateral congenital elbow dislocation; increasing the phenotypic spectrum of Steinfeld syndrome. Issue 3 (5th January 2016) - Jones, Gabriela E.; Robertson, Lisa; Maniyar, Amit; Shammas, Christos; Phelan, Marie M.; Vasudevan, Pradeep C.; Tanteles, George A.
Abstract : Steinfeld syndrome (MIM #184705) was first reported in 1982. It is characterised by holoprosencephaly and limb defects, however other anomalies may also be present. Following the initial description, three further cases have been reported in the literature. We report on a 23‐year‐old girl, with features of microform holoprosencephaly and bilateral congenital elbow dislocation in association with hypoplastic radial heads. She was identified to have a variant in the CDON gene inherited from her father who had ocular hypotelorism, but no other clinical features. We discuss the clinical features of Steinfeld syndrome, and broaden the phenotypic spectrum of this condition. Structural analysis suggests that this variant could lead to destabilisation of binding of CDON with hedgehog proteins. Further work needs to be done to confirm whether mutations in the CDON gene are the cause of Steinfeld syndrome. © 2016 Wiley Periodicals, Inc.